(untitled) (LACCEI, 2024)
The objective of this work was to optimize the ultrasound-assisted extraction conditions (time, temperature, and ethanol concentration) to obtain the maximum content of total phenolic compounds and antioxidant capacity from three asparagus by-products (woody ends, foliage, and discarded spears). For this, a rotatable central composite design (RCCD) was used. In addition, the stability under refrigerated storage and the application as a reducing agent for SiO2 nanoparticle synthesis were evaluated in extracts prepared with predicted optimal conditions. It was observed that the asparagus by-products are a great source of phenolic compounds with excellent antioxidant capacity, being the foliage the residue that presented the highest levels (almost 4 times more than the woody ends and 3 times more than the discarded spears). The conditions that allow maximizing the levels of both TPC and AC were for woody ends (25 °C, ethanol 62%, 5 min) for foliage (30 °C, ethanol 56%, 10min) and for discarded spears (48 °C, ethanol 69%, 27 min). Under the optimized conditions new extracts were elaborated, finding that the TPC and AC levels were 6198.95±136.98, 30058.48±635.27, 9621.76±100.29 μg GAE/g d.m and 9726.45±231.47, 37163.48±1082.59, 17579.01±397.55 μg Trolox/g d.m for woody ends, foliage, and discarded spears, respectively, which were similar to the predicted values and remained stable throughout 24 days of refrigerated storage. Finally, the application of the optimized extract from discarded spears was evaluated as a reducing agent in the process of synthesis of silica nanoparticles. The spectrophotometric characterization evidenced the formation of silica nanostructures, with possible mesoporous spherical morphology and semiconductor characteristics.